A Ten-Year Study of Drug Poisoning Cases Admitted to the Intensive Care Unit of 5 Azar Hospital in Gorgan, Iran - Mohammad Shokrzadeh; Reza Hoseinpoor; Danial Jafari; Azam Delaram; Akram Pouyan Sadr; Mehrnoosh Deylami; Yaghoub Shayeste (Golestan University Of Medical Sciences, 2019)
Background and objectives: Drug poisoning is a serious global health problem that sometimes requires hospitalization and intensive care. This study investigates clinical and demographic profile of acute poisoning cases admitted to the intensive care unit (ICU) of 5 Azar hospital in Gorgan, Iran. Methods: This cross-sectional descriptive study was carried out on 440 acute drug poisoning cases (224 men and 190 women) who had been admitted to the ICU of the hospital from March 2008 to March 2018. Data were collected with a checklist and using the census method. The collected data were analyzed using SPSS (version 16) and the Chi-square test. Results: Of 440 cases, 54.1% were male and 43.7% were aged 20-29 years. Suicide attempt by self-poisoning was the most important type of poisoning (70.8%). Benzodiazepines (38.9%) and narcotic drugs (18.6%) overdose was the most common cause of acute poisoning. The majority of incidents (72.7%) were caused by a single drug. The average length of stay in the ICU was 4.21 ± 3.45 days. Acute poisoning-related mortality rate was 4.1%, which was primarily due to the use of narcotic drugs. Conclusion: Benzodiazepines and narcotics are the primary agents involved in acute poisoning requiring critical care. Moreover, methadone-based narcotics are the main cause of drug poisoning-related mortality.